A toughened resin composition, a toughened layer, a prepreg, a laminate and a method of making and use thereof

CN117986841BActive Publication Date: 2026-10-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211342293.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-31
Publication Date
2026-10-30
Estimated Expiration
2042-10-31

AI Technical Summary

Technical Problem

[0005]针对现有技术存在的热塑性树脂增韧环氧树脂基体导致体系黏度高、对混合工艺和后续的涂膜等工艺要求高且浸渍纤维效果差,预浸料层间增韧导致预浸料粘性下降,以及层压板冲击后压缩强度低难以满足复合材料性能要求的问题,本发明提供一种新的增韧树脂,采用该增韧树脂制备的预浸料增韧层进而得到的预浸料和层压板,具有树脂基体黏度低、有利于工艺操作且浸渍效果好,本发明制备的增韧树脂且有较低的粘度,所以表面附有增韧层的预浸料在铺层过程中,预浸料之间保持粘性,互相可以黏结,等预浸料铺层固化后,增韧层会生成热塑性树脂,提高韧性,提升CAI,制备的层压板冲击后压缩强度高,复合材料的性能更好

Benefits of technology

[0042](1)本发明的树脂基体未进行本体增韧,而是把增韧成分做成增韧层,铺在预浸料表面,不会导致树脂基体黏度变大,导致浸渍纤维效果变差,增韧层体系黏度低于150Pa·s(70℃),有利于提升工艺操作性和对纤维的浸渍效果,避免产生因为浸渍不完全而引入的缺陷,导致复合材料性能下降。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003916652460000031
    Figure BDA0003916652460000031
  • Figure BDA0003916652460000091
    Figure BDA0003916652460000091
  • Figure BDA0003916652460000101
    Figure BDA0003916652460000101
Patent Text Reader

Abstract

The present application provides a toughened resin composition, a toughened layer, a prepreg, a laminate and a preparation method and application thereof. The toughened resin composition is prepared from raw materials including an epoxy resin, a blocked isocyanate and a thermoplastic resin; optionally, the prepreg toughened resin further comprises a catalyst; the laminate is prepared by making the toughened resin composition into a toughened layer, then into a prepreg with fibers, and then cutting, layering and curing the prepreg. The toughened resin composition system of the present application has low viscosity, is beneficial to process operation and has good impregnation effect; the toughened layer obtained by coating has adhesion in the prepreg layering process; after the prepreg is layered and cured, the prepared laminate has high compressive strength after impact and good toughness, and can be used for the preparation of various carbon fiber composite main load-bearing structures and non-load-bearing parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of toughening resins, and more specifically, to a toughening resin composition, a toughening layer, a prepreg, a laminate, a method for preparing the same, and its applications. Background Technology

[0002] Due to its advantages such as light weight, high strength, high modulus, and high designability, carbon fiber composites are increasingly used in the airframe structures of large civil aircraft. In some Airbus and Boeing models, composite materials account for more than half of the material's weight. Aircraft inevitably experience various impacts during use. When subjected to external impacts, metallic structures primarily absorb energy through plastic deformation at the impact site, while composite laminate structures absorb energy through elastic deformation and damage. Low-speed impacts are difficult to avoid in the use of composite components. Delamination of composite materials significantly reduces structural strength and stiffness, preventing the full realization of the lightweight advantages of composite materials and limiting further improvements in their application. Therefore, how to suppress delamination damage and improve the impact damage resistance and delamination resistance of composite laminates has become a research hotspot in aerospace composite materials. For aerospace-grade composite materials, the residual compressive strength after impact (CAI) is generally used to measure the toughness of the composite system.

[0003] High carbon fiber adhesive integrity (CAI) requires composite materials to possess high toughness, and the main ways to improve toughness are through toughening of the matrix resin and interlaminar toughening. For matrix resin toughening, thermoplastic resins are preferred as toughening agents, ensuring that the heat resistance of the composite material is not reduced while improving toughness. Hexcel's invention patent EP2607411 uses polyethersulfone (PES) resin and polyamide (PA) particles to composite toughen and modify an epoxy resin matrix. PES exists in the epoxy resin in a completely dissolved state, while PA particles exist in a dispersed state. Carbon fiber prepregs prepared using this toughened resin matrix show a significant improvement in CAI. Because the thermoplastic resin content is close to 30 wt%, the viscosity of this toughened resin matrix is ​​very high, placing high demands on the mixing process of the resin matrix and subsequent coating and prepreg processes. To address the problems of high resin system viscosity and reduced fiber impregnation effect caused by resin matrix toughening, the toughening component is localized in the interlaminar layer of the prepreg. Chinese invention patent CN104842619A discloses a manufacturing process for high-toughness multilayer prepreg. Based on a three-layer structure of resin layer-fiber layer-resin layer, one or more toughening layers are added. These toughening layers exist in the form of films, powders, or fabrics. The toughened composite material achieves a CAI of 260 MPa. While this toughening technology achieves good toughening results, it also brings other problems. To achieve high CAI, thermoplastic resin powder or films are added to the surface of the prepreg, causing one side of the prepreg to lose its adhesiveness. This loss of adhesiveness makes it difficult for the prepreg layers to bond and fix together during the layup process, resulting in poorer processability. Summary of the Invention

[0004] In order to solve the technical problems existing in the prior art, the present invention provides a toughening resin composition, a toughening layer, a prepreg, a laminate, a preparation method thereof, and its application.

[0005] To address the problems of existing technologies, such as high system viscosity due to thermoplastic resin toughening of epoxy resin matrix, high requirements for mixing and subsequent coating processes, poor fiber impregnation effect, reduced prepreg viscosity due to interlayer toughening of prepreg, and low post-impact compressive strength of laminate that fails to meet the performance requirements of composite materials, this invention provides a new toughening resin. Prepreg and laminates prepared using this toughening resin have low resin matrix viscosity, which facilitates process operation and provides good impregnation effect. The toughening resin prepared in this invention has a low viscosity, so the prepreg with the toughening layer on its surface maintains adhesion between prepreg layers during the layup process, allowing them to bond together. After the prepreg layup cures, the toughening layer generates thermoplastic resin, improving toughness and increasing CAI (compressive inert acid). The resulting laminate has high post-impact compressive strength, and the composite material has better performance.

[0006] One of the objectives of this invention is to provide a toughening resin composition.

[0007] The toughening resin composition is prepared from raw materials including epoxy resin, end-capped isocyanate and thermoplastic resin; optionally, the toughening resin composition further includes a catalyst; the epoxy resin is a room temperature liquid epoxy resin.

[0008] In a preferred embodiment of the present invention,

[0009] Based on 100 parts by weight of epoxy resin,

[0010]

[0011] This invention can be carried out without a catalyst. When isocyanates are capped with imidazole-based capping agents, the imidazole substances generated when the imidazole-based capping isocyanates are decapped upon heating can catalyze the reaction between epoxy resin and isocyanate. In this case, no catalyst is required.

[0012] In a preferred embodiment of the present invention,

[0013] The epoxy resin is at least one of glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, and modified epoxy resin thereof, where "therefore" refers to the above three types of epoxy resin; preferably, it is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, and modified epoxy resin thereof, where "therefore" refers to the above specific three types of epoxy resin.

[0014] The capped isocyanate is prepared from isocyanate and capping agent; the isocyanate is at least one selected from toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), hexamethylene diisocyanate (HDI), lysine diisocyanate (LDI), and polymethylene polyphenyl polyisocyanate (PAPI); the capping agent is at least one selected from imidazoles, phenols, alcohols, lactams, dicarbonyl hydrogen, oximes, and sodium bisulfite; the capping agent is preferably at least one selected from 2-methylimidazole, 2-ethyl-4-methylimidazole, imidazole, acetone oxime, and butanone oxime.

[0015] The catalyst is at least one of imidazole compounds, imidazole derivatives, tertiary amines, quaternary ammonium salts, metal halides, organometallic compounds, and Lewis acid / base complexes; the imidazole compound is at least one of imidazole, 1-methylimidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, and 2-phenylimidazole; the imidazole derivative is at least one of isocyanate or epoxy resin modified with imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, or 2-phenylimidazole.

[0016] The thermoplastic resin is at least one of polyethersulfone, polyetherimide, polyamide, polyimide, polyetheretherketone, polyetherketoneketone, and polysulfone; preferably, the particle size is 200-2000 mesh; more preferably, the particle size is 200-600 mesh.

[0017] In a preferred embodiment of the present invention,

[0018] The toughening resin composition has a viscosity of 15 Pa·s to 150 Pa·s at 70°C, preferably 20 Pa·s to 70 Pa·s.

[0019] A second objective of this invention is to provide a method for preparing a toughening resin composition, comprising:

[0020] The toughening resin composition is prepared by uniformly mixing the raw materials according to the specified dosage; the mixing temperature is preferably 30-110℃, more preferably 50-80℃.

[0021] A third objective of the present invention is to provide a toughening layer comprising the above-mentioned toughening resin composition.

[0022] The fourth objective of this invention is to provide a method for preparing a toughening layer, comprising coating the toughening resin composition to obtain the toughening layer.

[0023] The coating process includes, but is not limited to: pouring prepreg toughening resin into a coating machine and coating it onto release paper at 40–120°C.

[0024] The fifth objective of this invention is to provide a prepreg comprising the above-mentioned toughening layer.

[0025] The prepreg is made from raw materials including a resin matrix film, reinforcing fibers and the toughening layer;

[0026] Based on 100 parts by weight of reinforcing fiber,

[0027] 100 parts by weight of reinforcing fiber;

[0028] 10-120 parts by weight of resin matrix film; preferably 30-70 parts by weight;

[0029] The toughening layer comprises 5 to 50 parts by weight; preferably 10 to 25 parts by weight.

[0030] Preferably, the reinforcing fiber is at least one selected from carbon fiber, aramid fiber, glass fiber, and basalt fiber;

[0031] The resin-based film is prepared from raw materials including resin and curing agent; an accelerator may or may not be added. The resin is an epoxy resin and / or a modified epoxy resin, preferably at least one of glycidyl ether epoxy resin, glycidyl ester epoxy resin, and glycidylamine epoxy resin; the modified epoxy resin is at least one of modified epoxy resins of glycidyl ether epoxy resin, glycidyl ester epoxy resin, and glycidylamine epoxy resin; for example, but not limited to, at least one of E51 epoxy resin, XB9721 epoxy resin, and E51 modified epoxy resin; in this invention, the modification method can be determined as needed, for example, if an improvement in flame retardant properties is required, corresponding modification treatment can be performed. The curing agent is at least one of the following: amine curing agents, acid anhydride curing agents, linear phenolic curing agents, polyester resin curing agents, polyurethane curing agents, styrene-maleic anhydride copolymer resin curing agents, and polysulfide rubber curing agents; for example, but not limited to, at least one of diaminodiphenyl sulfone, diaminodiphenylmethane, acid anhydrides, and dicyandiamide. The accelerator is at least one of the following: amines, phenols, substituted urea 4102, imidazoles and their salts, boron trifluoride complexes, organometallic salts, and phosphine compounds; for example, but not limited to, at least one of DMP-30, 2-ethyl-4-methylimidazolium, N-p-chlorophenyl-N,N'-dimethylurea, boron trifluoride ethylamine, boron trifluoride triethylphosphine, boron trifluoride triisopropylphosphine, triphenylphosphine, phenol, resorcinol, and m-cresol.

[0032] With the total mass of the resin matrix film as 100%, the mass percentage of each raw material in the resin matrix film is as follows:

[0033] Resin content: 40-98%;

[0034] Curing agent 2-60%;

[0035] Accelerator 0-15%.

[0036] The sixth objective of this invention is to provide a method for preparing a prepreg, comprising:

[0037] The toughening layer is applied over the reinforcing fibers that have been impregnated with a resin matrix film to obtain the prepreg.

[0038] The seventh objective of this invention is to provide a laminate, which is prepared by cutting, laying, and curing the prepreg.

[0039] The curing process can be achieved through various methods, such as, but not limited to, thermal curing and photocuring. Thermal curing offers a wide range of curing conditions to achieve the desired curing, such as, but not limited to, 120℃ / 1h-180℃ / 2h.

[0040] An eighth objective of this invention is to provide an application of a toughening resin composition, a toughening layer, a prepreg, or a laminate in aerospace, military, or automotive applications. However, the applications are not limited to these.

[0041] The beneficial effects of this invention are:

[0042] (1) The resin matrix of the present invention is not toughened in bulk, but the toughening component is made into a toughening layer and laid on the surface of the prepreg. This will not cause the viscosity of the resin matrix to increase, resulting in a poor impregnation effect on the fiber. The viscosity of the toughening layer system is less than 150 Pa·s (70°C), which is beneficial to improving the process operability and the impregnation effect on the fiber, avoiding defects caused by incomplete impregnation, which would lead to a decline in the performance of the composite material.

[0043] (2) In the toughening layer of the present invention, the components are only mixed in the prepreg stage and the polymer is generated in the prepreg curing stage. During the layup, the epoxy resin and isocyanate do not react and the molecular weight is small, so the viscosity of the prepreg can be maintained, so that the prepreg has good layup properties. During the layup process, the prepregs are sticky and can bond with each other. The thermoplastic resin is generated when the layup is completed and cured, which provides toughness to the composite material. In contrast, the toughening layers of the prior art, such as thermoplastic fabrics, have a large molecular weight during the layup and poor resin viscosity, or thermoplastic particles are sprinkled on the surface of the prepreg, so the prepreg has no viscosity. Both of these situations will affect the toughness of the composite material after layup.

[0044] (3) The reaction product of the epoxy group of the epoxy resin and the isocyanate group of the end-capped isocyanate in the toughening layer of the present invention is a thermoplastic resin. Together with the added thermoplastic resin, it improves the toughness of the composite material and can significantly improve the compressive strength of the laminate after impact.

[0045] This invention solves the problem that toughening the epoxy resin matrix with thermoplastic resin in hot-melt prepregs leads to increased system viscosity, poor processability, and reduced impregnation effect on carbon fibers. This invention prepares a toughening layer by mixing epoxy resin and end-capped isocyanate, then adding thermoplastic resin. During the prepreg stage, this maintains the prepreg's viscosity, resulting in good lay-up properties and solving the problem of decreased prepreg viscosity caused by interlayer toughening. During the prepreg curing stage, a reaction occurs to generate toughening molecular chains, significantly improving the post-impact compressive strength of the laminate. This invention can be used in the fabrication of various carbon fiber composite load-bearing structures and non-load-bearing components. Detailed Implementation

[0046] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.

[0047] The raw materials used in the specific embodiments of the present invention are conventional commercially available raw materials.

[0048] Test method:

[0049] Prepreg was cut to appropriate sizes according to GB / T 21239-2007 standard, and laid up in a [45 / 0 / -45 / 90]S sequence. It was then placed in an autoclave for curing at 120℃ / 1h + 180℃ / 2h. After curing, the laminate was cut to obtain test samples with dimensions of 150mm × 100mm × 5mm. The samples were then subjected to post-impact compressive strength testing according to GB / T21239-2007 standard.

[0050] The viscosity of the toughening resin was tested using an advanced rotational rheometer (Anton Paar MCR302) with a cone-plate viscometer.

[0051] The parts in the examples and comparative examples refer to parts by weight.

[0052]

Example 1

[0053] 1) Preparation of end-capped isocyanates

[0054] Isophorone diisocyanate (IPDI) was blocked with 2-methylimidazole (2MI), with a molar ratio of secondary amine hydrogen atoms to isocyanate-NCO groups of 1.1:1. 2MI and IPDI were dissolved separately in chloroform to prepare 30% solutions. The system was protected under nitrogen purging. IPDI solution was added dropwise to the 2MI solution, and the temperature was raised to 55°C after the addition was complete. The infrared characteristic peaks of the isocyanate were monitored using infrared spectroscopy until they disappeared, at which point the reaction was terminated. The IPDI end-capped with 2MI was then dried by rotary evaporation for later use.

[0055] 2) Preparation of toughened resin composition

[0056] The formula consists of:

[0057] 100 parts by weight of 128 epoxy resin;

[0058] 110 parts by weight of the terminal isocyanate were obtained;

[0059] Polyethersulfone (400 mesh) 30 parts by weight;

[0060] A toughened resin composition was obtained by mixing 128 epoxy resin, end-capped isocyanate and polyethersulfone (400 mesh) and heating to 70°C to disperse evenly.

[0061] 3) Preparation of toughening layer

[0062] The toughening resin composition is placed in the resin tank of a coating machine, and the resin is uniformly coated onto the release paper at a coating temperature of 70°C to obtain a toughening layer.

[0063] 4) Preparation of resin matrix film

[0064] 4.1) The modified epoxy resin formulation consists of:

[0065] 128 epoxy resin: 70 parts by weight;

[0066] Four-functional epoxy resin XB9721: 30 parts by weight;

[0067] Bisphenol A: 20 parts by weight;

[0068] Triphenylphosphine: 0.1 parts by weight.

[0069] 4.2) The resin matrix film formulation consists of:

[0070] The resulting modified epoxy resin: 120 parts by weight;

[0071] 128 epoxy resin: 50 parts by weight;

[0072] 4,4'-Diaminodiphenyl sulfone: 45 parts by weight.

[0073] 4.3) Mixing Process Steps: 128 epoxy resin, tetrafunctional epoxy resin XB9721, and bisphenol A are heated to 120℃ to dissolve. Triphenylphosphine is added, and the mixture is heated to 180℃ and reacted for 3 hours to obtain a modified epoxy resin. Then, the modified epoxy resin, bisphenol A epoxy resin, and 4,4'-diaminodiphenyl sulfone are mixed at 70℃ to obtain the resin matrix.

[0074] Preparation of resin matrix film: Pour the above resin matrix into the resin tank of the coating machine, and coat the resin matrix evenly on the release paper at a coating temperature of 70°C.

[0075] 5) Preparation of high-toughness prepreg:

[0076] Prepreg was prepared using Toray T700×12k carbon fiber, with a weight ratio of reinforcing fiber:resin film:toughening layer of 100:30:25. Two rolls of matrix resin film were placed at the upper and lower unwinding stations at the front of the prepreg machine, respectively, while the toughening layer was placed at the unwinding station in the middle of the prepreg machine. At the first and second heating rollers and heating plate, the upper and lower matrix resin films impregnated the unidirectionally aligned carbon fibers. Then, the upper release paper was wound up, and the prepreg toughening layer was unwound from the middle unwinding station, covering the surface of the prepreg. The toughening layer was then bonded to the prepreg surface at the third heating roller and heating plate. After cooling on the cooling plate, the upper release paper was wound up, covered with a PE film, and finally, the prepreg was wound up.

[0077] 6) Toughening resin viscosity, laminate preparation and performance evaluation:

[0078] The viscosity of the toughening resin was tested using an advanced rotational rheometer (Anton Paar MCR302) with a cone-plate viscometer.

[0079] The prepreg was cut to appropriate sizes according to the requirements of GB / T 21239-2007 standard, and laid up in a [45 / 0 / -45 / 90]S sequence. It was then placed in an autoclave for curing at 120℃ for 1 hour followed by 180℃ for 2 hours. After curing, the laminate was cut to obtain test samples with dimensions of 150mm × 100mm × 5mm. The samples were then subjected to post-impact compressive strength testing according to GB / T21239-2007 standard. The results are shown in Table 1.

[0080]

Example 2

[0081] 1) Preparation of end-capped isocyanates

[0082] Diphenylmethane diisocyanate (MDI) was blocked with methyl ethyl ketone oxime (MEKO), with a MEKO to isocyanate-NCO molar ratio of 1.05:1. MEKO and MDI were dissolved separately in acetone to prepare 50% (w / w) solutions. The system was protected under nitrogen purging. MDI solution was added dropwise to the MEKO solution, and the temperature was raised to 60°C after the addition was complete. The reaction was stopped by detecting the characteristic infrared peaks of isocyanate in the system using infrared spectroscopy until they disappeared. The MEKO-blocked MDI product was then dried by rotary evaporation for later use.

[0083] 2) Preparation of toughened resin composition

[0084] The formula consists of:

[0085]

[0086] A toughened resin composition was obtained by mixing 128 epoxy resin, end-capped isocyanate and polyethersulfone (400 mesh) and heating to 70°C to disperse evenly.

[0087] 3) Preparation of toughening layer

[0088] The toughening resin composition is placed in the resin tank of a coating machine, and the resin is uniformly coated onto the release paper at a coating temperature of 70°C to obtain a toughening layer.

[0089] 4) Preparation of resin matrix film

[0090] The preparation of the resin matrix film is the same as in Example 1.

[0091] 5) Preparation of high-toughness prepreg:

[0092] Prepreg was prepared using Toray T700×12k carbon fiber, with a weight ratio of reinforcing fiber:resin film:toughening layer of 100:30:25. Two rolls of matrix resin film were placed at the upper and lower unwinding stations at the front of the prepreg machine, respectively, while the toughening layer was placed at the unwinding station in the middle of the prepreg machine. At the first and second heating rollers and heating plate, the upper and lower matrix resin films impregnated the unidirectionally aligned carbon fibers. Then, the upper release paper was wound up, and the prepreg toughening layer was unwound from the middle unwinding station, covering the surface of the prepreg. The toughening layer was then bonded to the prepreg surface at the third heating roller and heating plate. After cooling on the cooling plate, the upper release paper was wound up, covered with a PE film, and finally, the prepreg was wound up.

[0093] 6) Toughening resin viscosity, laminate preparation and performance evaluation:

[0094] The viscosity of the toughening resin was tested using an advanced rotational rheometer (Anton Paar MCR302) with a cone-plate viscometer.

[0095] The prepreg was cut to appropriate sizes according to the requirements of GB / T 21239-2007 standard, and laid up in a [45 / 0 / -45 / 90]S sequence. It was then placed in an autoclave for curing at 120℃ for 1 hour followed by 180℃ for 2 hours. After curing, the laminate was cut to obtain test samples with dimensions of 150mm × 100mm × 5mm. The samples were then subjected to post-impact compressive strength testing according to GB / T21239-2007 standard. The results are shown in Table 1.

[0096]

Example 3

[0097] 1) Preparation of end-capped isocyanates

[0098] The preparation method of isophorone diisocyanate (IPDI) blocked with 2-methylimidazole (2MI) is the same as in Example 1;

[0099] The preparation method of blocking diphenylmethane diisocyanate (MDI) with butanone oxime is the same as in Example 2.

[0100] 2) Preparation of toughened resin composition

[0101] The formula consists of:

[0102]

[0103] A toughened resin composition was obtained by mixing 128 epoxy resin, end-capped isocyanate and polyethersulfone (400 mesh) and heating to 70°C to disperse evenly.

[0104] 3) Preparation of toughening layer

[0105] The toughening resin composition is placed in the resin tank of a coating machine, and the resin is uniformly coated onto the release paper at a coating temperature of 70°C to obtain a toughening layer.

[0106] 4) Preparation of resin matrix film

[0107] The preparation method of the resin matrix film is exactly the same as that in the example.

[0108] 5) Preparation of high-toughness prepreg:

[0109] Prepreg was prepared using Toray T700×12k carbon fiber, with a weight ratio of reinforcing fiber:resin film:toughening layer of 100:30:25. Two rolls of matrix resin film were placed at the upper and lower unwinding stations at the front of the prepreg machine, respectively, while the toughening layer was placed at the unwinding station in the middle of the prepreg machine. At the first and second heating rollers and heating plate, the upper and lower matrix resin films impregnated the unidirectionally aligned carbon fibers. Then, the upper release paper was wound up, and the prepreg toughening layer was unwound from the middle unwinding station, covering the surface of the prepreg. The toughening layer was then bonded to the prepreg surface at the third heating roller and heating plate. After cooling on the cooling plate, the upper release paper was wound up, covered with a PE film, and finally, the prepreg was wound up.

[0110] 6) Toughening resin viscosity, laminate preparation and performance evaluation:

[0111] The viscosity of the toughening resin was tested using an advanced rotational rheometer (Anton Paar MCR302) with a cone-plate viscometer.

[0112] The prepreg was cut to appropriate sizes according to the requirements of GB / T 21239-2007 standard, and laid up in a [45 / 0 / -45 / 90]S sequence. It was then placed in an autoclave for curing at 120℃ for 1 hour followed by 180℃ for 2 hours. After curing, the laminate was cut to obtain test samples with dimensions of 150mm × 100mm × 5mm. The samples were then subjected to post-impact compressive strength testing according to GB / T21239-2007 standard. The results are shown in Table 1.

[0113]

Example 4

[0114] The laminate was prepared according to the method of Example 2, except that the catalyst used in step 2) of preparing the toughening resin composition was replaced with 2-ethyl-4-methylimidazole, and the amount was the same as 3 parts by weight.

[0115] The other raw materials, dosages, and preparation processes in Example 4 are the same as those in Example 2.

[0116] The viscosity of the toughening resin and the performance of the laminate were evaluated, and the results are shown in Table 1.

[0117]

Example 5

[0118] The laminate was prepared according to the method of Example 2, the difference being that the catalyst used in step 2) of preparing the toughening resin composition was replaced with 2-ethyl-4-methylimidazolium and HDI modifier, and the amount was still 3 parts by weight.

[0119] Preparation method of 2-ethyl-4-methylimidazolium modified with HDI:

[0120] The molar ratio of 2-ethyl-4-methylimidazole to HDI was 2:1. 2-ethyl-4-methylimidazole and HDI were each prepared as 50% chloroform solutions. At room temperature, under nitrogen protection, the HDI solution was added dropwise to the 2-ethyl-4-methylimidazole solution. After the addition was complete, the system was heated to 60°C and reacted for 3 hours. The product was then rotary evaporated under reduced pressure to obtain the 2-ethyl-4-methylimidazole and HDI modified product.

[0121] The other raw materials, dosages, and preparation processes in Example 5 are the same as those in Example 2.

[0122] The viscosity of the toughening resin and the performance of the laminate were evaluated, and the results are shown in Table 1.

[0123]

Example 6

[0124] The laminate was prepared according to the method of Example 2, the difference being that in step 2), the catalyst used in the preparation of the toughening resin composition was replaced with 2-ethyl-4-methylimidazolium and epoxy modifier, and the amount was 6 parts by weight.

[0125] Preparation method of 2-ethyl-4-methylimidazolium and epoxy modified compound:

[0126] The molar ratio of 2-ethyl-4-methylimidazole to 128 epoxy resin was 1:1. 2-ethyl-4-methylimidazole and 128 epoxy resin were each prepared as 50% xylene solutions. At room temperature, under nitrogen protection, the 128 epoxy resin solution was added dropwise to the 2-ethyl-4-methylimidazole solution. After the addition was complete, the system was heated to 100℃ and reacted for 2 hours. The product was then rotary evaporated under reduced pressure to obtain 2-ethyl-4-methylimidazole and HDI modified product.

[0127] The other raw materials, dosages, and preparation processes in Example 6 are the same as those in Example 2.

[0128] The viscosity of the toughening resin and the performance of the laminate were evaluated, and the results are shown in Table 1.

[0129]

Example 7

[0130] The laminate was prepared according to the method of Example 1, except that in step 2), the amount of end-capped isocyanate in the toughening resin composition was 70 parts by weight.

[0131] The other raw materials, dosages, and preparation processes in Example 7 are the same as those in Example 1.

[0132] The viscosity of the toughening resin and the performance of the laminate were evaluated, and the results are shown in Table 1.

[0133]

Example 8

[0134] The laminate was prepared according to the method of Example 1, except that in step 2), the amount of end-capped isocyanate used in the toughening resin composition was 130 parts by weight.

[0135] The other raw materials, dosages, and preparation processes in Example 8 are the same as those in Example 1.

[0136] The viscosity of the toughening resin and the performance of the laminate were evaluated, and the results are shown in Table 1.

[0137]

Example 9

[0138] The laminate was prepared according to the method of Example 1, the difference from Example 1 being that: in step 2), the epoxy resin in the formulation for preparing the toughening resin composition was 70 parts by weight of 128 epoxy resin and 30 parts by weight of 9721 epoxy resin.

[0139] The other raw materials, dosages, and preparation processes in Example 9 are the same as those in Example 1.

[0140] The viscosity of the toughening resin and the performance of the laminate were evaluated, and the results are shown in Table 1.

[0141]

Example 10

[0142] The laminate was prepared according to the method of Example 1, the difference being that in step 2), the amount of polyethersulfone in the formulation for preparing the toughening resin composition was 10 parts by weight.

[0143] The other raw materials, dosages, and preparation processes in Example 10 are the same as those in Example 1.

[0144] The viscosity of the toughening resin and the performance of the laminate were evaluated, and the results are shown in Table 1.

[0145]

Example 11

[0146] The laminate was prepared according to the method of Example 1, the difference being that in step 2), the amount of polyethersulfone in the formulation for preparing the toughening resin composition was 40 parts by weight.

[0147] The other raw materials, dosages, and preparation processes in Example 11 are the same as those in Example 1.

[0148] The viscosity of the toughening resin and the performance of the laminate were evaluated, and the results are shown in Table 1.

[0149]

Example 12

[0150] The laminate was prepared according to the method of Example 1, the difference from Example 1 being that in step 2), the polyethersulfone was replaced with polyetheretherketone (400 mesh) in the formulation for preparing the toughening resin composition, and the amount was the same as 30 parts by weight.

[0151] The other raw materials, dosages, and preparation processes in Example 12 are the same as those in Example 1.

[0152] The viscosity of the toughening resin and the performance of the laminate were evaluated, and the results are shown in Table 1.

[0153]

Example 13

[0154] The laminate was prepared according to the method of Example 1, except that in step 2), the polyethersulfone was replaced with polysulfone (400 mesh) in the formulation for preparing the toughening resin composition, and the amount was the same as 30 parts by weight.

[0155] The other raw materials, dosages, and preparation processes in Example 13 are the same as those in Example 1.

[0156] The toughening resin viscosity and the performance of the laminate were evaluated according to the method in Example 1, and the results are shown in Table 1.

[0157]

Example 14

[0158] The laminate was prepared according to the method of Example 1, the difference being that in step 2), the polyethersulfone in the formulation for preparing the toughening resin composition was 250 mesh.

[0159] The other raw materials, dosages, and preparation processes in Example 14 are the same as those in Example 1.

[0160] The viscosity of the toughening resin and the performance of the laminate were evaluated, and the results are shown in Table 1.

[0161]

Example 15

[0162] The laminate was prepared according to the method of Example 1, the difference being that in step 2), the polyethersulfone in the formulation for preparing the toughening resin composition was 550 mesh.

[0163] The other raw materials, dosages, and preparation processes in Example 15 are the same as those in Example 1.

[0164] The viscosity of the toughening resin and the performance of the laminate were evaluated, and the results are shown in Table 1.

[0165]

Example 16

[0166] The laminate was prepared according to the method of Example 1, the difference being that the mixing temperature was 50°C when preparing the toughening resin composition; and the weight ratio of reinforcing fiber: resin film: toughening layer was 100:70:10 when preparing the prepreg.

[0167] The other raw materials, dosages, and preparation processes in Example 16 are the same as those in Example 1.

[0168] The viscosity of the toughening resin and the performance of the laminate were evaluated, and the results are shown in Table 1.

[0169]

Comparative Example 1

[0170] The laminate was prepared according to the method of Example 1, except that no toughening layer was added.

[0171] The preparation method is as follows:

[0172] 1) Preparation of resin matrix film

[0173] The preparation method of the resin matrix film is exactly the same as that in Example 1.

[0174] 2) Preparation of high-toughness prepreg:

[0175] Prepreg was prepared using Toray T700×12k carbon fiber. Two rolls of matrix resin film were placed on the upper and lower unwinding stations at the front of the prepreg machine, respectively. At the first, second, and third heating rollers and heating plate, the upper and lower layers of matrix resin film impregnated the unidirectionally arranged carbon fibers. After cooling by the cooling plate, the upper release paper was wound up, covered with PE film, and finally the prepreg was wound up.

[0176] 3) Laminate preparation and performance evaluation:

[0177] Laminates were prepared according to the method in Example 1 and their performance was evaluated. The results are shown in Table 1.

[0178] [Comparative Example 2]

[0179] The laminate was prepared according to the method of Example 1, the difference being that the toughening resin composition formulation and the matrix resin film formulation were the same.

[0180] The other raw materials, dosages, and preparation processes of Comparative Example 2 were the same as those of Example 1.

[0181] The viscosity of the toughening resin and the performance of the laminate were evaluated, and the results are shown in Table 1.

[0182] The performance of the toughening resin viscosity and the prepared laminates in Examples 1-16 and Comparative Examples 1-2 was evaluated, and the results are shown in Table 1.

[0183] Table 1. Test results of toughening resin viscosity and post-impact compressive strength of laminate.

[0184]

[0185] The toughening resin compositions of Examples 1-16 have a viscosity of 21 Pa·s to 67 Pa·s at 70°C, which is beneficial for improving processability and the impregnation effect on fibers.

[0186] Compared with Comparative Example 2, the laminate prepared in Example 1 had a post-impact compressive strength of 321 MPa, while that in Comparative Example 2 was 232 MPa. This is because the toughening layer used in the toughening resin composition of Comparative Example 2 was the matrix resin film cured product prepared in Example 1. The toughness of the matrix resin film cured product was worse than that of the toughening resin cured product, resulting in less absorption of impact energy, more severe delamination of the laminate, and lower post-impact compressive strength.

[0187] Compared with Comparative Example 1, the laminate prepared in Comparative Example 1 had a post-impact compressive strength of 164 MPa, which was much lower than that in Example 1, proving that the toughening layer played a key role in improving the toughness of the laminate.

[0188] The laminates prepared in Examples 1-16 have a post-impact compressive strength of 216-322 MPa, demonstrating that the toughening layer prepared by the toughening resin composition of the present invention can significantly improve the post-impact compressive strength of the laminate after curing.

Claims

1. A toughening resin composition prepared from raw materials including epoxy resin, end-capped isocyanate and thermoplastic resin; optionally, the toughening resin composition further includes a catalyst; wherein the epoxy resin is a room temperature liquid epoxy resin; Based on 100 parts by weight of epoxy resin, 100 parts by weight of epoxy resin; 20-180 parts by weight of capped isocyanate; 5-100 parts by weight of thermoplastic resin; The particle size of the thermoplastic resin is 200~2000 mesh.

2. The toughening resin composition according to claim 1, characterized in that: Based on 100 parts by weight of epoxy resin, 100 parts by weight of epoxy resin; 50-150 parts by weight of capped isocyanate; 10-40 parts by weight of thermoplastic resin; Catalyst 0-20 parts by weight.

3. The toughening resin composition according to claim 2, characterized in that: Based on 100 parts by weight of epoxy resin, 100 parts by weight of epoxy resin; 70-130 parts by weight of capped isocyanate; Catalyst 2-7 parts by weight.

4. The toughening resin composition according to claim 1, characterized in that: The epoxy resin is at least one of glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, and modified epoxy resin thereof; and / or, The terminated isocyanate is prepared from isocyanate and terminating agent; the isocyanate is at least one selected from toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, and polymethylene polyphenyl polyisocyanate; the terminating agent is at least one selected from imidazoles, phenols, alcohols, lactams, dicarbonyl hydrogen, oximes, and sodium bisulfite; and / or, The catalyst is at least one of imidazole compounds, imidazole derivatives, tertiary amines, quaternary ammonium salts, metal halides, organometallic compounds, and Lewis acid / base complexes; the imidazole compound is at least one of imidazole, 1-methylimidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, and 2-phenylimidazole; the imidazole derivative is at least one of isocyanate or epoxy resin modified with imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, or 2-phenylimidazole; and / or, The thermoplastic resin is at least one of polyethersulfone, polyetherimide, polyamide, polyimide, polyetheretherketone, polyetherketoneketone, and polysulfone.

5. The toughening resin composition according to claim 4, characterized in that: The epoxy resin is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, and modified epoxy resins thereof; and / or, The capping agent is at least one selected from 2-methylimidazole, 2-ethyl-4-methylimidazole, imidazole, acetone oxime, and butanone oxime; and / or, The particle size of the thermoplastic resin is 200-600 mesh.

6. The toughening resin composition according to any one of claims 1 to 5, characterized in that: The toughening resin composition has a viscosity of 15 Pa at 70ºC. s~150Pa s.

7. The toughening resin composition according to claim 6, characterized in that: The toughening resin composition has a viscosity of 20 Pa at 70ºC. s~70Pa s.

8. A method for preparing a toughening resin composition according to any one of claims 1 to 7, comprising: The toughening resin composition is prepared by uniformly mixing the raw materials according to the specified amounts.

9. The method for preparing the toughening resin composition according to claim 8, characterized in that: The mixing temperature is 30~110℃.

10. The method for preparing the toughening resin composition according to claim 9, characterized in that: The mixing temperature is 50~80℃.

11. A toughening layer comprising the toughening resin composition according to any one of claims 1 to 7, or the toughening resin composition prepared by the method according to any one of claims 8 to 10.

12. A method for preparing the toughening layer as described in claim 11, comprising coating the toughening resin composition to obtain the toughening layer.

13. A prepreg comprising the toughening layer of claim 11, made from raw materials including a resin matrix film, reinforcing fibers and the toughening layer; Based on 100 parts by weight of reinforcing fiber, 100 parts by weight of reinforcing fiber; 10-120 parts by weight of resin matrix film; 5-50 parts by weight of toughening layer.

14. The prepreg as described in claim 13, characterized in that: Based on 100 parts by weight of reinforcing fiber, 100 parts by weight of reinforcing fiber; 30-70 parts by weight of resin matrix film; 10-25 parts by weight of toughening layer.

15. The prepreg as described in claim 13 or 14, characterized in that: The reinforcing fiber is at least one of carbon fiber, aramid fiber, glass fiber, and basalt fiber; and / or the resin is epoxy resin and / or modified epoxy resin.

16. A method for preparing a prepreg as described in any one of claims 13 to 15, comprising: The toughening layer is applied over the reinforcing fibers that have been impregnated with a resin matrix film to obtain the prepreg.

17. A laminate comprising the prepreg according to any one of claims 13 to 15, wherein the prepreg is cut, laid up and cured to obtain the laminate.

18. The application of a toughening resin composition as described in any one of claims 1 to 7, a toughening layer as described in claim 11, a prepreg as described in any one of claims 13 to 15, and a laminate as described in claim 17 in aerospace, military, or automotive applications.

Citation Information

Patent Citations

  • Prepreg manufacturing process of high-tenacity multilayer structure

    CN104842619A

  • Improvements in or relating to fibre reinforced materials

    EP2607411A1

  • Prepreg, product and preparation method thereof

    CN110067150A

  • Prepreg toughening resin, prepreg toughening layer, prepreg as well as preparation method and application of prepreg

    CN114479358A